(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The work forms a new breakthrough scientific trend in the management of safety and quality in the economics based on the introduction of new objects and management criteria, new knowledge and models, new tasks, special software and digital management. The paper offers the new management objects: State authorities, socioeconomic systems and projects, process quality management in the socio-economic life of a person, the safe living space. We use the management criteria of safety and quality. The paper introduces the new knowledge for management in economics: the methodology of safety and quality, new types of Boolean events-propositions, scenarios of systems failure, new types of logical-probabilistic models, results of research of various systems and educational program. New management tasks are also considered, special software are described and the essence of digital management in economics is stated.